2022
DOI: 10.1021/acscatal.2c01529
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-Catalyzed Ring Expansion Reactions for the Concise Construction of Densely Functionalized Oxathionines and Oxathiocines

Abstract: Ring expansion reactions have been proven to be efficient tools for building medium-sized rings with broad applications in synthetic and medicinal chemistry. However, the strategy involving pericyclic or pseudopericyclic pathways via sulfur ylide-initiated [1,4]-sigmatropic rearrangement remains an under-exploited area. Herein, we disclose an interesting ring expansion of thiochromenes and aromatic thiophenes via rhodium catalysis, which enables the straightforward assembly of polyaromatic oxathionines and oxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…16 However, this methodology could not be used for the transformation of diaryl chalcogenide ethers as starting materials, which are more commercially available. 17 During the course of our ongoing studies on carbene chemistry and the synthesis of chalcogenide compounds, we wondered whether [1,4]-aryl migration of chalcogenide ylides could be achieved. We envisioned that the reaction of diaryl chalcogenide ethers with metal carbene would afford ylide IC, which should lead to the formation of vinyl product 3 via a Smiles rearrangement (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…16 However, this methodology could not be used for the transformation of diaryl chalcogenide ethers as starting materials, which are more commercially available. 17 During the course of our ongoing studies on carbene chemistry and the synthesis of chalcogenide compounds, we wondered whether [1,4]-aryl migration of chalcogenide ylides could be achieved. We envisioned that the reaction of diaryl chalcogenide ethers with metal carbene would afford ylide IC, which should lead to the formation of vinyl product 3 via a Smiles rearrangement (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Koenig reported sulfide homologation using an enamine fragment that involves the [1,4]-migration of an alkyl group, while Murakami, Wang, and Liu reported rhodium-catalyzed [1,4]-acyl transfer reactions that use triazoles, 3-diazoindol-2-imines, and diazoketones as carbene precursors. Recently, Wang et al described the rhodium-catalyzed dearomative ring-expansion reactions of thiochromenes and aromatic thiophenes involving sulfur-ylide-initiated [1,4]-alkenyl/aryl transfer …”
mentioning
confidence: 99%
“…Recently, Wang et al described the rhodium-catalyzed dearomative ring-expansion reactions of thiochromenes and aromatic thiophenes involving sulfur-ylideinitiated [1,4]-alkenyl/aryl transfer. 16 The above-mentioned methodologies are confined to the use of thioether or thioester substrates, in which the transformations are largely limited to C−S bond cleavage and C−X (X = C, N, O) bond formation. We expected to harness the power of the metal carbene and the good nucleophilicity of the thiocarbonyls to generate sulfur ylides in a facile and catalytic fashion and trigger remote group shift behavior.…”
mentioning
confidence: 99%
“…Recently, our group demonstrated that the Rh(II)-catalyzed carbene N−H insertion strategy could enable highly atroposelective access to axially chiral N-arylindolocarbazoles. 8d Given the importance of axial-spiro chirality and our continuous interest in carbene chemistry, 18 we envisaged that the high enantioinduction of C−N coupling could further realize the dynamic kinetic resolution of unique spiroacetal 3indolinone racemates. To our knowledge, the simultaneous construction of the chiral C−N axis and spiro stereocenter in complex atropisomers from simple building blocks in a single step remains unprecedented.…”
mentioning
confidence: 99%